Role and applications of advanced digital technologies in achieving sustainability in multimodal logistics operations: A systematic literature review - Anaiz Gul Fareed; Fabio De Felice; Antonio Forcina; Antonella Petrillo (Sustainable Futures, 2024)
Integration of advanced digital technologies along with ensuring environmental sustainability in the logistics sector is becoming the need of the hour novel multimodal transportation concept. The rapid technological development in the era of industry 4.0 can not only create new opportunities in achieving highly efficient, intelligent, and smart logistics systems but also enable new business models for value addition, additionally, this novel system will also avoid environmental degradation and use of scarce natural resources that contribute to climate change. This paper summarizes the research trends of these technologies in multimodal logistics systems since 2005 through a systematic literature review. The results revealed a mixed picture of the situation, starting from emerging technologies like artificial intelligence, machine learning, and blockchain becoming key technological concepts for multimodal logistics systems to government policy hurdles and lack of impact breakthroughs in the industry. However, the results show that adaptation to these technologies improves the overall environmental, economic, and social sustainability of the system.